Needs for nurses to provide spiritual care and their associated influencing factors among elderly inpatients with stroke in China: A cross-sectional quantitative study. Issue 3 (June 2022) - Wang, Zhangyi; Zhao, Haomei; Zhu, Yue; Zhang, Siai; Xiao, Luwei; Bao, Haiqin; Wang, Zhao; Wang, Yue; Li, Xuechun; Zhang, Yajun; Pang, Xiaoli
Abstract: Objectives: To investigate the spiritual care needs and associated influencing factors among elderly inpatients with stroke, and to examine the correlations among spiritual care needs, spiritual well-being, self-perceived burden, self-transcendence, and social support. Methods: A cross-sectional quantitative design was implemented, and the STROBE Checklist was used as the foundation of the study. A convenience sample of 458 elderly inpatients with stroke was selected from three hospitals in China. The sociodemographic characteristics questionnaire, the Nurse Spiritual Therapeutics Scale, the Functional Assessment of Chronic Illness Therapy—Spiritual Well-being, the Self-Perceived Burden Scale, the Chinese Self-Transcendence Scale, and the Perceived Social Support Scale were used. Descriptive statistics, correlation, Student's t -test, ANOVA, non-parametric, and multiple linear regression analyses were used to analyze the data. Results: The total score of spiritual care needs was 29.82 ± 7.65. Spiritual care needs were positively correlated with spiritual well-being ( r = 0.709, p < 0.01), self-transcendence ( r = 0.710, p < 0.01), and social support ( r = 0.691, p < 0.01), whereas being negatively correlated with self-perceived burden ( r = −0.587, p < 0.01). Religious beliefs, educational level, residence place, disease course, spiritual well-being, self-perceived burden, self-transcendence, and social support were found to be the main influencing factors. Significance of results: The spiritual care needs were prevalent and moderate. It is suggested that nurses should enhance spiritual care knowledge and competence, take targeted spiritual care measures according to inpatients' individual personality traits or characteristics and differences of patients, reduce their self-perceived burden and improve their spiritual well-being, self-transcendence and social support in multiple ways and levels, so as to meet their spiritual care needs to the greatest extent and enhance their spiritual comfort.